The Health Care Transition of Youth With Liver Disease Into the Adult Health System: Position Paper From ESPGHAN and EASL. Issue 6 (June 2018) - Vajro, Pietro; Fischler, Björn; Burra, Patrizia; Debray, Dominique; Dezsofi, Antal; Guercio Nuzio, Salvatore; Hadzic, Nedim; Hierro, Loreto; Jahnel, Joerg; Lamireau, Thierry; McKiernan, Patrick; McLin, Valerie; et al.
ABSTRACT: Background: Medical advances have dramatically improved the long-term prognosis of children and adolescents with once-fatal hepatobiliary diseases. However, there is no generally accepted optimal pathway of care for the transition from paediatric care to the adult health system. Aim: The purpose of this position paper is to propose a transition process for young people with paediatric onset hepatobiliary diseases from child-centred to adult-centred healthcare services. Methods: Seventeen ESPGHAN/EASL physicians from 13 countries (Austria, Belgium, France, Germany, Hungary, Italy, the Netherlands, Norway, Poland, Spain, Sweden, Switzerland, and United Kingdom) formulated and answered questions after examining the currently published literature on transition from childhood to adulthood. PubMed and Google Scholar were systematically searched between 1980 and January 2018. Quality of evidence was assessed by the Grading of Recommendation Assessment, Development and Evaluation (GRADE) system. Expert opinions were used to support recommendations whenever the evidence was graded weak. All authors voted on each recommendation, using the nominal voting technique. Results: We reviewed the literature regarding the optimal timing for the initiation of the transition process and the transfer of the patient to adult services, principal documents, transition multi-professional team components, main barriers, and goals of the general transition process. A transition plan based on available evidence was agreed focusing on the individual young people's readiness and on coordinated teamwork, with transition monitoring continuing until the first year of adult services. We further agreed on selected features of transitioning processes inherent to the most frequent paediatric-onset hepatobiliary diseases. The discussion highlights specific clinical issues that will probably present to adult gastrointestinal specialists and that should be considered, according to published evidence, in the long-term tracking of patients. Conclusions: Transfer of medical care of individuals with paediatric onset hepatobiliary chronic diseases to adult facilities is a complex task requiring multiple involvements of patients and both paediatric and adult care providers. Abstract : Supplemental Digital Content is available in the text